The blood pressure sensitivity to changes in sodium intake is similar in Asians, Blacks and Whites. An analysis of 92 randomized controlled trials - Graudal, Niels; Jürgens, Gesche (Frontiers in Physiology, 2015)
The purpose of the meta-analysis of randomized trials was to analyze the significance of ethnicity on the effect of sodium reduction (SR) on blood pressure (BP) by estimating the effect of SR on BP in Asians, Blacks and Whites under conditions, which were adjusted with respect to baseline BP, baseline sodium intake and quantity of SR. Relevant studies were retrieved from a pool of 167 RCTs published in the period 1973-2010 and identified in a previous Cochrane review. 9 Asian, 9 Black and 74 White populations standardized with respect to the range of baseline blood pressure, the range of baseline sodium, duration of SR (at least 7 days) and baseline sodium intake (at maximum 250 mmol) intake were included. In the cross-sectional analysis, there was no difference in change in SBP to SR between the ethnic groups, but there was a small difference in SR induced change in DBP between Blacks and Whites (p = 0.04). The comparison of changes in SBP and DBP to SR in ethnic groups compared in identical settings showed no statistically significant differences between the groups.